Assessment Quality in Mathematics Learning: An Analysis of Critical Thinking Instruments for Derivative Topics - Amini, Nurul; Arliani, Elly (Jurnal Ilmiah Profesi Pendidikan, 2025)
The assessment of students' critical thinking abilities is crucial for the learning process; however, numerous educators have been unable to select high-quality evaluation tools. A question that is effective must satisfy the following criteria: adequate validity, reliability, difficulty level, differentiating power, and effectiveness of the checker. A quantitative approach was employed in this study, which employed descriptive methods in one of the high schools in Yogyakarta. 15 summative test items on derivative material were administered to 30 students as the research subjects. The question is declared valid, as the content validity results using V-Aiken's indicate a value of 0.8889. This value is classified as high. The reliability test yielded a value of 0.924 for choice questions and 0.777 for description questions, suggesting that the questions were reliable. The analysis of the items revealed that item number 6 required deletion due to its low differential power, while item number 7 required revision. Questions 10 and 12 should be addressed in accordance with the level of difficulty. The exemptions are ineffective, necessitating revision of the answer options in question numbers 9 and 10. This research underscores the significance of enhancing evaluation instruments to facilitate the attainment of student learning indicators.